Avirulence of LT2 strains of Salmonella typhimurium results from a defective rpoS gene. - Swords, W E (1997)
In order to identify the genetic basis for the attenuation of Salmonella typhimurium LT2 strains, experiments were performed to identify a gene(s) which restores virulence to an avirulent LT2 strain. These and further experiments confirmed that an rpoS mutation is the sole determinant of the attenuation of S. typhimurium LT2.